BRIKET RAMAH LINGKUNGAN DARI BATANG PINANG: PENGARUH TEKANAN HIDROLIK TERHADAP KECEPATAN PEMBAKARAN - Waine, Jefri; Haurissa, Jusuf; Mini, Mathina (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Sains dan Teknologi Jayapura, 2025)
This study aims to analyze the effect of hydraulic pressure variation on the thermal characteristics of briquettes made from areca palm stem waste (Areca catechu), particularly in terms of material density, heat conduction rate, and calorific value. The briquettes were molded in a box shape using pressures of 60, 80, and 100 kg/cm². The test results show that increasing the pressing pressure is directly proportional to the increase in the heat conduction rate (q), which were 0.2635 W, 0.2772 W, and 0.2867 W, respectively. In parallel, the calorific value also increased from 5124 kcal/kg to 5245 kcal/kg. This is due to increased density and reduced porosity of the material under high pressure, which strengthens interparticle bonding and enhances heat transfer paths. The analysis indicates a trend of diminishing thermal performance gains at the highest pressure level, suggesting a saturation point in material compaction. The study concludes that a pressing pressure of 100 kg/cm² yields optimal thermal results and improves the combustion quality and energy efficiency of areca palm briquettes. These findings contribute to the utilization of local biomass as an environmentally friendly and sustainable alternative energy source.